2019
DOI: 10.1002/app.48677
|View full text |Cite
|
Sign up to set email alerts
|

Gradient crystallinity and its influence on the poly(vinylidene fluoride)/poly(methyl methacrylate) membrane‐derived by immersion precipitation method

Abstract: Herein, phase inversion poly(vinylidene fluoride)/poly(methyl methacrylate) (PVDF/PMMA) microporous membranes were prepared at various PMMA concentration by immersion precipitation method. Increment in the PMMA concentration has a significant influence in the PVDF membrane crystallinity, which is studied by differential scanning calorimeter, X-ray diffractometer, and smallangle X-ray scattering analyses. Properties such as membrane bulk structure, porosity, hydrophilicity, mechanical stability, and water flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 99 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…It is common for these polymer mixtures to be incompatible, resulting in a granular structure due to the stress between the combined phases. A study conducted by Remanan et al showed that, through the ultrasonic integration of a TiO 2 /chitosan/GO nanocomposite filler, the resulting membrane notably improved its defense against bacterial adherence and fouling [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is common for these polymer mixtures to be incompatible, resulting in a granular structure due to the stress between the combined phases. A study conducted by Remanan et al showed that, through the ultrasonic integration of a TiO 2 /chitosan/GO nanocomposite filler, the resulting membrane notably improved its defense against bacterial adherence and fouling [29].…”
Section: Introductionmentioning
confidence: 99%